Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Light parameters and iron ions regulate mass-independent fractionation via modulating degradation pathways of methylmercury - Kun Zhang; Lin Yang; Deming Han; Cailing Xiao; Yongguang Yin; Ligang Hu; Yong Liang; Jianbo Shi; Guibin Jiang (Water Research, 2026)

Patterns and mechanisms of cross-media antimicrobial resistance development in a typical reclaimed water-receiving urban river - Bang-Ze Li; Shu-Hao Du; Han-Lin Cui; Xin-Xin Gao; Jia-Hao Wu; Bei-Ying Li; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Investigation of the effect of storage duration on aroma transformation in Shoumei white tea - Zhiyuan Lin; Han Yan; Longyu Guo; Jiakun Peng; Ying Wang; Jianjian Gao; Jiatong Wang; Huimin Jiang; Ying Wang; Liang Zeng; Yin Zhu; Zhi Lin; et al. (Food Chemistry, 2026)

Enhanced phenanthrene degradation in microalgae-bacteria systems: Mechanistic roles of exogenous and indigenous degraders - Mengying Wang; Han Wang; Xuetao Liang; Jingran Li; Chen Wang; Longyan Cui; Shuo Yang; Jiaxuan Lin; Qi Yang; Zhilin Yang (Bioresource Technology, 2026)

Integrative study of acute ammonia exposure on the skin of the Striped catfish (Pangasianodon hypophthalmus) - Wei-Hsuan Hsiao; Shun-Yi Lin; Ying-Hsien Wu; Han-Chen Ho; Tsunglin Liu; Liang-Chun Wang (Aquatic Toxicology, 2026)

Exposure to a porcine appeasing pheromone in periparturient sows: Effects on behavior, health status, and reproductive performance - Shuang Liu; Liang Wang; Xu-Kai Nie; Chun-Yu Song; Ying-Han Chen; Lin Wang; Cai-Yu Lian (Applied Animal Behaviour Science, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Transforming waste copper slag into a nitrogen-doped mesoporous catalyst for singlet oxygen-dominated peroxymonosulfate activation toward efficient and sustainable degradation of rhodamine B - Ying Zhang; Chunjie Huang; Ying Lin; Xingyong Xue; Lihong Lan; Yaocong Han; Qiaoqiao Su; Jinlu Liang; Dongping Wei; Linqiang Mo (Environmental Research, 2026)

Multichannel epicardial bioelectronics via a stretchable, wet-adhesive, antibacterial hydrogel with highly conformable Interface - Si Shen; Xingyun Fan; Weibin Liang; Chenghua Xie; Nian Zhang; Pengqi Wang; Rurong Lin; Jie Zhang; Yanni Han; Chongyin Qiu; Shiqi Guo; Jingxing Dai; et al. (Chemical Engineering Journal, 2026)

An intelligent nanosystem for disrupting the neuro-immune-oncology axis to unleash anti-tumor “immune storm” - Yuanhang Han; Yunxiang Ding; Yuyang Wang; Zhiqiang Yang; Xiaoxiao Liang; Xin Wang; Yushen Lu; Ruimin Wang; Zhenyi Chen; Yifan Hu; Lin Cai; Jianbin Xu; et al. (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Impacts of carbonaceous aerosols from summer crop residue burning on air quality, radiation and meteorology over east China - Yuanyuan Zheng; Jian Wu; Zhiwei Han; Jiawei Li; Jie Li; Yunfei Wu; Jing Wang; Lin Liang (Theoretical and Applied Climatology, 2026)

Alnustone ameliorates obesity and polycystic ovary syndrome by remodeling adipose metabolism via AMPK signaling - Yiming Qin; Shourui Hu; Yanqi Xu; Zongxuan Lin; Xiaofan Liang; Yue Liu; Yuxuan Li; Chunxuan Geng; Xiangyan Chen; Xizi Feng; Zi-Jiang Chen; Han Zhao; et al. (Science China Life Sciences, 2026)

Nighttime growth in the green tide alga Ulva prolifera: metabolic basis and ecological implications - Han Xu; Mingzi Lin; Jiaying Bian; Dongyi Yang; Jianan Jiang; Shenyuan Liang; Hao Zhang; Wenrong Zhu; Nianjun Xu; Yahe Li (Journal of Applied Phycology, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Contrasting Effects of Nitrogen Input on Soil Carbon Pools in Arid and Humid Climates - Shibing Jia; Cuihuan Li; Zhenfeng Xu; Bo Tan; Xinglei Cui; Guopeng Liang; Han Li; Li Zhang; Lin Xu; Hongwei Xu; Sining Liu; Lixia Wang; et al. (Global Change Biology, 2026)
Nitrogen (N) input affects soil organic carbon (SOC) dynamics and storage by specifically influencing the light (LFOC) and heavy fractions of organic C (HFOC). While the effects of N input on SOC pools are known, its specific influence in arid and humid regions remains unresolved, although it is critically important to predict carbon–climate feedback and SOC accumulation. We conducted a meta‐analysis of 881 paired observations from 60 studies to quantify the climate‐specific responses of SOC, LFOC, and HFOC contents to N input, thereby revealing distinct effects in arid versus humid regions. N input increased the LFOC content by 25% in arid regions, whereas the HFOC and SOC contents remained unchanged. This LFOC accumulation may reflect increased plant C inputs, suppressed microbial decomposition, and strong physical protection compared with soil without N input. Conversely, in humid regions, N input increased the HFOC and SOC contents by 10%. These increases were associated with the following four mechanisms: (1) increases in plant and microbial necromass production after N input, (2) microbially‐mediated formation of the HFOC from the LFOC, (3) accelerated lignin‐derived C accumulation due to suppressed saprotrophic fungal decomposition, and (4) raised physico–chemical stabilization by various biotic and abiotic mechanisms. Specifically, increases in LFOC content in arid regions occurred under medium to high N input rates (≥ 50 kg N ha −1 year −1 ), whereas increases in HFOC and SOC contents in humid regions occurred only under medium N input (50–100 kg N ha‐1 year −1 ). These increases occurred primarily after periods of N input longer than 5 years and mainly in topsoil (

Impact of polystyrene nanoplastics on soil microbial biomass - Chunyang Li; Heping Shang; Zeyu Cai; Weili Jia; Yini Cao; Xiupei Zhou; Jie Zhang; Sixiang Zhuang; Ziqin Lin; Anqi Liang; Lanfang Han; Jason C. White; et al. (Environmental Chemistry Letters, 2026)

Valorization of baghouse dust from lime industry through carbonation processes - Hung-Chieh Liang; Cheng-You Lin; Hsing-Jung Ho; Cheng-Han Lee (Waste Management, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Ce-Fe-MI/CA composite catalyst for catalytic ozonation: Synergistic adsorption-activation via Ce/Fe sites & oxygen vacancies and application in air flotation-catalytic ozonation coupling process for pharmaceutical wastewater - Lin Yue; Shiqi Xing; Xiaoyun Han; Wang Liang; Yanfang Liu; Xinyang Liang; Yonghui Han (Journal of Environmental Chemical Engineering, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Exploration of salivary biomarkers for accurate diagnosis of anxiety, depression, and somatic symptom disorder by the integration of microfluidic chip and machine learning - Rongjie Wang; Fei Xu; Lin Wang; Xue Zhang; Miao Huang; Zhun Wei; Yan Jiang; Yunhong Zhang; Xiaoshuang Chen; Yanbo Liang; Yu Zhang; Xueqin Mao; et al. (Chemical Engineering Journal, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Seismic performance of trussed concrete-filled steel tubular (CFST) hybrid structures: Experiments - Zhan-Shuo Liang; Lin-Hai Han; Ming Xiao (Engineering Structures, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Size-dependent effects of polystyrene Nanoplastics on hepatic Immunometabolism and the gut-liver Axis in the Swamp Eel (Monopterus albus) - Mingming Han; Wenzong Zhou; Ji Liang; Aileen Tan Shau-Hwai; Zihan Zhou; Lin Cheng; Jiayuan Liao; Weiwei Huang; Qichen Jiang; Weiwei Lv (Aquaculture, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Electric field superposition for efficient implantable ultrasound energy harvesting - Aokai Yang; Chaoran Tan; Yuyang Lin; Haoying Han; Renfei Wei; Yan Wang; Kang Chen; Shizhe Lin; Liang Huang; Jun Zhou (Chemical Engineering Journal, 2026)

Identification of an allotetraploid hybrid (Pengze crucian carp (♀) × Xingguo red carp (♂)) and its transcriptomic responses to herpesvirus infection - Shujia Liao; Yingshi Tang; Han Wen; Honghai Liang; Guanghong Song; Jingfeng Liu; Mingqing Zhang; Zixuan E; Danqi Lu; Haoran Lin; Shuisheng Li; Yong Zhang (Aquaculture, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Dominant governing mechanisms of deformation-seepage and dynamic evolution model of permeability in gas-containing coal under coupled stress-pore pressure - Chongzhi Wang; Bin Zhou; Shugang Li; Haifei Lin; Haiqing Shuang; Dongming Zhang; Shoujian Peng; Liang Cheng; Han Yang (Fuel, 2026)

Characteristics of benthic microeukaryotic communities in different ecosystems of the Yellow River Estuary salt marshes - Jing Han; Lin Sun; Junrong Liang; Yahui Gao; Changping Chen (Estuarine, Coastal and Shelf Science, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Do river-valley breezes enhance evaporation over the Three Gorges Reservoir during periods with negative water-to-air temperature differences? - Songjun Han; Baozhong Zhang; Lei Wang; Jiajia Liu; Weijie Wang; Taotao Lin; Jidong Wang; Liang Wei; Zhijun Jia (Journal of Hydrology, 2025)

Dendrobium officinale polysaccharide inhibits M1 macrophage polarization via activating SENP1-SIRT3 signaling and alleviates ulcerative colitis - Jing Zhang; Xiaohe Lin; Huaying Song; Yumin Xie; Shaozhen Hou; Song Huang; Xianhua Du; Hailun Li; Yun Han; Jian Liang; Xiaoyan Jiang (Food Research International, 2025)

Acute skin responses to ammonia in striped catfish (Pangasianodon hypophthalmus) unveil a potential damage-buffering mechanism - Wei-Hsuan Hsiao; Shun-Yi Lin; Tsung-Lin Liu; Han-Chen Ho; Liang-Chun Wang (Fish & Shellfish Immunology, 2025)

Morphological, histological and multi-omics analysis revealed the molecular response of female western mosquitofish (Gambusia affinis) to levonorgestrel exposure - Kaichun Chen; Tongfu Lu; Weijian Chen; Shengyue Lin; Dingxian Chen; Shuzheng Ye; Weiqian Liang; Sixun Li; Binhua Deng; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Reduction of antibiotics and antibiotic resistance genes in simulated-sunlight-supported counter-diffusion bacteria-Algae biofilms: Interface properties and functional gene responses - Han Zhang; Jiao Yin; Haotian Jiang; Weichen Zeng; Yufei Cheng; Jiaxuan Yang; Dachao Lin; Langming Bai; Heng Liang (Water Research, 2025)

Sustainable and safe biochar-based composites from ZIF-8 and artificial humic acid for enhanced environmental remediation of Cu(II) and tetracycline in water - Shuang Gai; Lin Han; Xinru Xu; Zhiyuan Feng; Fangjun Lou; Wenbo Liang; Fan Yang (Process Safety and Environmental Protection, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Effects of Angelica sinensis polysaccharides on growth performance, antioxidant capacity, immune response, intestinal microbiota, and liver transcriptome in Mauremys mutica - Zike Yan; Jingu Shi; Kaijie Lin; Yuhan Li; Yutian Zhan; Mingzuo Gao; Hongyao Zhang; Shuyu Han; Jingzhen Liang (Aquaculture International, 2025)

Biofilm response in potential difference-enhanced membrane-aerated biofilm systems for accelerated antibiotic removal and ARG mitigation - Han Zhang; Haotian Jiang; Jiao Yin; Tianyi Wang; Weichen Zeng; Dachao Lin; Boyan Xu; Langming Bai; Heng Liang; How Yong Ng (Water Research, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

A novel hydrogel electrolyte for self-powered sensing and safe energy storage systems in extreme environments - Wen Jiang; Yang Tao; Qiuxiang Yang; Yudong Wang; Lin Peng; Ce Zhang; Shounian Cheng; Jiandan Liang; Yu Han; Xia Cao (Chemical Engineering Journal, 2025)

Levonorgestrel-induced anal fin masculinization in mosquitofish: Do TGF-β/BMP signaling and osteogenic remodeling underpin endocrine disruption in aquatic ecosystem? - Weiqian Liang; Tongfu Lu; Dingxian Chen; Weijian Chen; Kaifeng Wang; Jie Lai; Shengyue Lin; Lin Gui; Jian Gong; Chong Han; Qiang Li (Aquatic Toxicology, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

An efficient network with state space model under evidential training for fetal echocardiography standard view recognition - Changzhao Chen; Yiman Liu; Tongtong Liang; Shibin Lin; Xiaoxiang Han; Xiaohong Liu; Jing Yang; Yuqi Zhang; Xueping Yan (Medical & Biological Engineering & Computing, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Lipid profiling of Toxoplasma tachyzoites and the mouse host - Lijun Shi; Lin Liang; Wenchao Li; Cun Liu; Kun Han; Xinghui Zhao; Zhanzhong Zhao (Veterinary Parasitology, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Dual-emission fluorescent probe with sequential two-step ESIPT activation mechanism for selective hydrazine detection and multifunctional applications - Hanxun Zou; Guoming Lin; Yuxuan Bao; Jie Liang; Yunyun Li; Lifeng Cai; Han-Ying Wu; Fan Yang; Hang Chen; Xiuchun Lin; Yi-Hong Xiao; Lei Yang; et al. (Journal of Hazardous Materials, 2025)

Effect of water vapor on the structure and performance of silver catalysts for ethylene oxidation - Yandong Chu; Hongmei Liang; Qiang Lin; Haoyang Huang; Ping Che; Yongsheng Han (Chemical Engineering Journal, 2025)

Enhancing growth, pigment composition, polysaccharides, fatty and amino acid content in Ulva prolifera by manipulating temperature, light intensity, and photoperiod - Xuan Zhou; Mingzi Lin; Jianan Jiang; Shenyuan Liang; Han Xu; Wenrong Zhu; Nianjun Xu; Yahe Li (Aquaculture, 2025)

Efficient antibiotic tetracycline degradation and toxicity abatement via the perovskite-type CaFexNi1-xO3 assisted heterogeneous electro-Fenton system - Yuling Liang; Aochen Feng; Naif Abdullah Al-Dhabi; Jing Zhang; Wenle Xing; Tao Chen; Yuxuan Han; Guangming Zeng; Lin Tang; Wangwang Tang (Water Research, 2025)

Performance of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to eccentric compression - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2025)

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Thermal-enhanced deep removal of multiple impurities upon pH induction towards selective regeneration of high-purity iron phosphate - Yaohui Xie; Fen Zhang; Shuyu Xiang; Guang Yang; Lin Qu; Fei Han; Liang Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

The heterogeneous response in leaf traits among seasons and plant types of an evergreen broadleaf forest in western China to nitrogen addition was regulated by fertilization intensity - Wenzheng Chang; Qiu Song; Tianxing Liang; Jie Chen; Lixia Wang; Han Li; Li Zhang; Chengming You; Hongwei Xu; Lin Xu; Bo Tan; Zhenfeng Xu; et al. (Plant and Soil, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Co-combustion reaction of corn stalk hydrochar and anthracite: Kinetics, mechanism and CO2 emission reduction - Wang Liang; Yihao Cui; Di Zhu; Yihan Chen; Yonghui Han; Lin Yue; Chunhe Jiang; Runsheng Xu; Xiaojun Ning; Jianliang Zhang; Chuan Wang; Guangwei Wang (Fuel, 2025)

Electrostatic-Induced Crystal-Rearrangement of Benzoquinones Cathode for Large-Scale All-Organic Aqueous Proton Batteries - Jianyong Zhang; Jingyuan Yu; Wenwei Zhang; Ahmed Eissa Abdelmaoula; Chunhua Han; Zhenzhen Dou; Feng Liang; Lin Xu (Chemical Engineering Journal, 2025)

Reversal of Extreme Drought-Induced Plant Nitrogen and Phosphorus Imbalances in Grassland - Xiao-Sa Liang; Zheng-Wen Wang; Wentao Luo; Lin Song; Wang Ma; Niwu Te; Qiang Yu; Xing-Guo Han; Xiao-Tao Lü (Ecosystems, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Establishing electro-functionalized gravity-driven ceramic membrane filtration (EGDCM) for decentralized treatment of algae-laden brackish water: Comparison of in-situ electro-oxidation and ex-situ electro-coagulation - Dachao Lin; Xinxu Shen; Caiwei Tan; Han Zhang; Rui Chen; Xing Du; Heng Liang (Water Research, 2025)

Recent advances in antibiotic removal using independent and coupled microbial fuel cells (MFCs): Mechanisms and cells (MFCs): Mechanisms and practical applications - Liye Liang; Yingzi Lin; Ruijun Ren; Qingjing Zhang; Jiangqi Qu; Yuanhao Liu; Zhe Han; Xin Sun (Journal of Water Process Engineering, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Performance and calculation of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to bending - Zhan-Shuo Liang; Lin-Hai Han; Pu Wang (Engineering Structures, 2025)

Graphene quantum dots decorated organic conductive polymer for advanced ternary amorphous solar-blind UV photovoltaic photodetectors - Han Cai; Haolin Yang; Weisen Li; Jiarong Liang; Zhuogeng Lin; Xingui Tang; Yanghui Liu; Dan Zhang; Wei Zheng (Chemical Engineering Journal, 2025)

Triboelectric materials with UV protection, anti-bacterial activity, and green closed-loop recycling for medical monitoring - Jiandan Liang; Qiuxiang Yang; Ce Zhang; Wen Jiang; Shounian Cheng; Yang Tao; Lin Peng; Yu Han; Xia Cao; Zhong Lin Wang (Chemical Engineering Journal, 2025)

Risk hotspots and influencing factors identification of heavy metal(loid)s in agricultural soils using spatial bivariate analysis and random forest - Xiaohang Xu; Zhidong Xu; Longchao Liang; Jialiang Han; Gaoen Wu; Qinhui Lu; Lin Liu; Pan Li; Qiao Han; Le Wang; Sensen Zhang; Yanhai Hu; et al. (Science of The Total Environment, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Modulating charge transfer and constructing synergistic bimetallic active sites for CO-SCR reactions in inverse spinel - Qin Li; Xiaorong Han; Lin Tao; Qiuju Qin; Xuechi Du; Yuzhu Liang; Bin Li; Zhengjun Chen; Liya Zhou; Lihui Dong (Journal of Environmental Chemical Engineering, 2024)

Late Triassic orogenic gold mineralization along the northwest margin of the Indochina Block: Revealed from calcite U-Pb ages and geochemistry of the Phapon gold deposit, Laos - Linnan Guo; Yanwen Tang; Lin Hou; Shusheng Liu; Chunmei Huang; Zhiwei Han; Siwei Xu; Zhibo Luo; Huimin Liang (Journal of Asian Earth Sciences, 2024)

Impacts of distinct residual aluminum on gypsum scaling in nanofiltration: Identification of key species - Jinjin Jia; Jinlong Wang; Dachao Lin; Jing Zhao; Hesong Wang; Longfeng Hu; Jiaxuan Yang; Han Zhang; Guibai Li; Heng Liang (Desalination, 2024)

Electron-deficient wastewater treatment in membrane-aerated conductive biofilm reactor: Performance and mechanism - Weijia Gong; Han Zhang; Minghao Xue; Lin Guo; Mengmeng Jiang; Yuzhou Zhao; Heng Liang (Bioresource Technology, 2024)

The source, transport, deposition and direct radiative effect of mineral dust over western China: A modeling study of July 2022 with focus on the Tibetan Plateau - Lin Liang; Zhiwei Han; Weiwei Chen; Jiawei Li; Mingjie Liang; Shujing Shen (Atmospheric Research, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Similarity characterization of geotechnical engineering sites under the site-specific data scenario - Liang Han; Mingjing Jiang; Wengang Zhang; Lin Yang (Bulletin of Engineering Geology and the Environment, 2024)

Mathematical modeling and comparative metabolomics analyses of interactions between Lactiplantibacillus plantarum and Morganella morganii - Jing Han; Binkun Liu; Xinping Lin; Sufang Zhang; Liang Dong; Chaofan Ji (Food Research International, 2024)

Enhancement of stress resistance of electroactive biofilms against hypersaline shock via exogenous electron mediator addition - Tao Li; Chen-ying Li; Han-lin Liang; Xiao-xue Li; Xiao-li Yang; Hua Li; Hai-liang Song (Chemical Engineering Journal, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Construction of Cu2-xS@Zn0.5Cd0.5S S-scheme heterojunction with core-shell structure for efficient photocatalytic hydrogen production and tetracycline degradation - Zhiqiang Ai; Xiaoya Zhu; Liwei Lin; Han Li; Yanan Wang; Qian Liang; Man Zhou; Song Xu; Zhongyu Li (Journal of Environmental Chemical Engineering, 2024)

Novel catalytic membrane based on γ-FeOOH@PVDF/peroxymonosulfate for efficient ammonia recovery: Self-cleaning mechanism and emerging organic contaminant degradation performance - Wucheng Ma; Chenfei Liu; Liang Zhu; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Shi Wang; Lin Chen; Yiping Li (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Cryopreservation-enhanced differentiation capacity of embryogenic cultures of Castanea mollissima - Shuangxian Liu; Liang Lin; Biao Han; Junchao Ma; Hugh W. Pritchard; Xiaojian Hu; Min Deng; Hongying Chen (Cryobiology, 2024)

Corrigendum to “A comprehensive comparison of copula models and multivariate normal distribution for geo-material parametric data” [Comput. Geotech. 164 (2023) 105777] - Liang Han; Haijun Liu; Wengang Zhang; Lin Wang (Computers and Geotechnics, 2024)

Sedimentary characteristics and development model of the bedded evaporites in the Paleogene Kumugeliemu formation, Kuqa depression, Northwestern China - Liang Luo; Jingxiang Guo; Chenlin Hu; Huixi Lin; Jonathan Atuquaye Quaye; Xuewen Zhou; Bo Han (Carbonates and Evaporites, 2024)

Performances of full-scale biological nitrogen pre-treatment process for drinking water source: Seasonal variations and microbial community - Hai-Hsuan Cheng; Yee Han Hew; Yi-Ju Wu; Tin-Yin Chen; Yi Ting Chiu; Li Ying Chen; Tsair-Fuh Lin; Liang-Ming Whang (Chemosphere, 2024)

Preharvest GA3 treatment at optimized time points enhanced the storability of ‘Shixia’ longan fruit - Tao Luo; Libing Long; Tingting Lai; Xiaolan Lin; Chenning Ning; Ziying Lai; Xinxin Du; Liang Shuai; Dongmei Han; Zhenxian Wu (Postharvest Biology and Technology, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

A new species of Populus and the extensive hybrid speciation arising from it on the Qinghai-Tibet Plateau - Yu-Jie Shi; Jia-Xuan Mi; Jin-Liang Huang; Fei-Fei Tian; Fang He; Yu Zhong; Han-Bo Yang; Fang Wang; Yu Xiao; Lin-Kai Yang; Fan Zhang; Liang-Hua Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Impacts of open biomass burning in Southeast Asia on atmospheric PM2.5 concentrations over south China from 2009 to 2018 - Jie Li; Wenxuan Fan; Jian Wu; Zhiwei Han; Jiawei Li; Chuwei Zhang; Lin Liang (Atmospheric Environment, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Advanced oxidation process/coagulation coupled with membrane distillation (AOP/Coag-MD) for efficient ammonia recovery: Elucidating biofouling control performance and mechanism - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Linting Zhao; Lin Chen; Liang Zhu (Journal of Hazardous Materials, 2024)

Self-assembled C-Ag hybrid nanoparticle on nanoporous GaN enabled ultra-high enhancement factor SERS sensor for sensitive thiram detection - Hongpeng Zhou; Jiaoyan Qiu; Yunhong Zhang; Yanbo Liang; Lin Han; Yu Zhang (Journal of Hazardous Materials, 2024)

Assessment and management for future habitat risks under the implementation of China's territorial spatial planning: A case study from Hainan Island - Xiaolin Zhang; Xiaobin Jin; Xinyuan Liang; Xu Shi; Rui Sun; Wenjie Zhu; Jinhuang Lin; Bo Han; Yinkang Zhou (Environmental Impact Assessment Review, 2024)

MazF-rolling circle amplification combined MALDI-TOF MS for site-specific detection of N6-methyladenosine RNA - Guobin Han; Qiuyuan Lin; Jia Yi; Qian Lyu; Qingwei Ma; Liang Qiao (Analytica Chimica Acta, 2024)

Chromosomal mapping of a major genetic locus from Agropyron cristatum chromosome 6P that influences grain number and spikelet number in wheat - Yida Lin; Shenghui Zhou; Wenjing Yang; Bing Han; Xuezhong Liang; Yuxin Zhang; Jinpeng Zhang; Haiming Han; Baojin Guo; Weihua Liu; Xinming Yang; Xiuquan Li; et al. (Theoretical and Applied Genetics, 2024)

Slc43a2+ T cell metastasis from spleen to brain in RGNNV infected teleost - Qing Wang; Yali Liu; Minlin Zhang; Min Yang; Jiantao Liang; Xiaoling Zuo; Shaowen Wang; Xianze Jia; Huihong Zhao; Han Jiang; Qiang Lin; Qiwei Qin (Science China Life Sciences, 2024)

Alternation of social behaviors for zebrafish (Danio rerio) in response to acute cold stress - Sian-Tai Liu; Chun-Yung Chang; Kuang-Yung Lee; Sok-Keng Tong; Han-Liang Huang; Hsi Chen; Jiun-Lin Horng; Ming-Yi Chou (Fish Physiology and Biochemistry, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

In vitro assessment of the bacterial stress response and resistance evolution during multidrug-resistant bacterial invasion of the Xenopus tropicalis intestinal tract under typical stresses - Xiaojun Lin; Ruiqi Han; Taojie Liang; Chaonan Zhang; Yanbin Xu; Huishi Peng; Xiao Zhou; Lu Huang (Journal of Hazardous Materials, 2024)

Trussed concrete-filled steel tubular hybrid structures subjected to axial compression: Performance and design calculation - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

The CropGPT project: Call for a global, coordinated effort in precision design breeding driven by AI using biological big data - Wanchao Zhu; Rui Han; Xiaoyang Shang; Tao Zhou; Chengyong Liang; Xiaomeng Qin; Hong Chen; Zaiwen Feng; Hongwei Zhang; Xingming Fan; Weifu Li; Lin Li (Molecular Plant, 2024)

Magnetic biochar enhanced copper immobilization in agricultural lands: Insights from adsorption precipitation and redox - Wucheng Ma; Rui Han; Wei Zhang; Hao Zhang; Lin Chen; Liang Zhu (Journal of Environmental Management, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Emergence of OXA-48-producing hypervirulent Klebsiella pneumoniae strains in Taiwan - Yi-Tsung Lin; Chien Chuang; Sheng-Hua Chou; Chih-Han Juan; Tsuey-Ching Yang; Barry N. Kreiswirth; Liang Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

The impact of urbanization on urban flood risk of Nakhon Ratchasima, Thailand - Apinan Seemuangngam; Han-Liang Lin (Applied Geography, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Clinical characteristics and outcomes of patients with COVID-19 and tuberculosis coinfection - Jun Lv; Mengyu Liang; Lin Wang; Minmin Zhang; Renjie Liu; Han Liang; Chen Wang; Liuqun Jia; Qinglei Zeng; Pengfei Zhu (Infectious Diseases, 2023)

New insights into the influence of pre-oxidation on membrane fouling during nanofiltration of brackish water considering inorganic-organic complexation and oxidant reduction byproducts - Dachao Lin; Han Zhang; Zhihong Wang; Daliang Xu; Guibai Li; Mathias Ulbricht; Heng Liang (Science of The Total Environment, 2023)

Application of novel nanobubble-contained electrolyzed catalytic water to cleanup petroleum-hydrocarbon contaminated soils and groundwater: A pilot-scale and performance evaluation study - Wing-Sze Ho; Wei-Han Lin; Francis Verpoort; Kun-Liang Hong; Jiun-Hau Ou; Chih-Ming Kao (Journal of Environmental Management, 2023)

Molecular cloning, expression, and functional analysis of a putative lectin from the pearl oyster (Pinctada fucata, Gould 1850) - Peng Liu; Wenyue Li; Yue Peng; Siyin Han; Zhongxiu Liang; Yanhui Cen; Xinrong Li; Peiyan Wang; Huiying Lv; Qingying Zhang; Honglin Chen; Jiang Lin (Fish & Shellfish Immunology, 2023)

A comprehensive comparison of copula models and multivariate normal distribution for geo-material parametric data - Liang Han; Haijun Liu; Wengang Zhang; Lin Wang (Computers and Geotechnics, 2023)

Covalent organic frameworks for modulating crystallization kinetics in perovskite photovoltaics - Xiao Liang; Chaoqin Han; Fei Wang; Jiajun Wu; Xianfang Zhou; Haoran Lin; Xiaoyuan Liu; Quanyao Zhu; Gang Li; Hanlin Hu (Chemical Engineering Journal, 2023)

Peroxymonosulfate enhanced Fe(III) coagulation coupled with membrane distillation for ammonia recovery: Membrane fouling control process and mechanism - Wucheng Ma; Rui Han; Liang Zhu; Wei Zhang; Hao Zhang; Longjie Jiang; Lin Chen (Desalination, 2023)

Nanoscale photocatalytic hydrogen production system mitigates inflammation by harnessing glycolysis waste - Cheng-Yu Wu; Cam-Hoa Mac; Tung-Han Yang; Khanh Nguyen; Shih-Kai Lo; Yen Chang; Po-Liang Lai; Hsing-Wen Sung; Yu-Jung Lin (Chemical Engineering Journal, 2023)

Responses of bacterial community composition and diversity to multi-level nitrogen addition at different periods of growing season driven by conditional rare taxa in an alpine meadow - Yilun Hu; Hasbagan Ganjurjav; Guozheng Hu; Guoxu Ji; Lin Han; Yubao Sha; Yan Liang; Qingzhu Gao (Biology and Fertility of Soils, 2023)

High-performance nanofiltration concentrate treatment by a five-chamber bioelectrochemical system - Jialin Liang; Fan Zhong; Han Lin; Xubin Ma; Jun Lan; Bo Ye; Lei Zhang (Journal of Environmental Management, 2023)

Effects of filter cartridge wetted before filtration and during filtration on the performance of cartridge dust collector - Shihang Li; Liyuan Liu; Xiaoyu Tan; Hao Liu; Changgeng Gui; Xingyue Chen; Muze Han; Yihan Lin; Jiang Shao; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

High water content electrically driven artificial muscles with large and stable deformation for soft robots - Chunbao Liu; Hui Xu; Yunhong Liang; Suqian Ma; Zhaohua Lin; Lei Ren; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Investigation of additive-assisted microbial-induced calcium carbonate precipitation in 3D printed cross fractures - Liang Guo; Min Zhang; Mingwei Liao; Baoquan Wang; Xiaoyu He; Yiqi Peng; Xingzhu Lin; Ni He; Zhuhong Xiong; Han Chen; Yehui Shi; Tong Li (Geomechanics for Energy and the Environment, 2023)

Hydrochromic wood biocomposites for humidity and moisture detection - Yujie Chen; Chaozheng Liu; Zhaolun Liang; Lei Ye; Lin Liu; Zhipeng Liu; Xinhao Feng; Lloyd Donaldson; Tripti Singh; Xianxu Zhan; Jingquan Han; Qiliang Fu; et al. (Chemical Engineering Journal, 2023)

Hydrothermal characteristics of the Mienhua submarine volcano in the southernmost Okinawa trough - Tzu-Ting Chen; Ho-Han Hsu; Chih-Chieh Su; Char-Shine Liu; Yunshuen Wang; Song-Chuen Chen; Emmy T. Y. Chang; Feng-Hsin Hsu; Liang-Fu Lin; Jih-Hsin Chang; Jyun-Nai Wu; Ta-Wei Hsu; et al. (Marine Geophysical Research, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Distribution and dissipation laws of excess pore water pressure based on pile-soil interface during pile-sinking in saturated clay - Yonghong Wang; Jiamin Jin; Bo Han; Yishun Jiang; Dongsheng Jeng; Huining Liu; Zuodong Liang; Lin Cui (Soil Dynamics and Earthquake Engineering, 2023)

m6A writer WTAP targets NRF2 to accelerate bladder cancer malignancy via m6A-dependent ferroptosis regulation - Ke Wang; Gang Wang; Gang Li; Wei Zhang; Yarong Wang; Xiaofeng Lin; Chengxian Han; Hanxuan Chen; Liang Shi; Abudoula Reheman; Jingkai Li; Zhaomin Li; et al. (Apoptosis, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Radiative effects and feedbacks of anthropogenic aerosols on boundary layer meteorology and fine particulate matter during the COVID-19 lockdown over China - Mingjie Liang; Zhiwei Han; Jiawei Li; Yele Sun; Lin Liang; Yue Li (Science of The Total Environment, 2023)

Potential negative effects of illumination on gravity-driven membrane system in treating sulfamethoxazole-containing water - Rui Chen; Han Zhang; Dachao Lin; Jinlong Wang; Yuanqing Guo; Xiaobin Tang; Weijia Gong; Heng Liang (Resources, Conservation and Recycling, 2023)

Origins of black carbon from anthropogenic emissions and open biomass burning transported to Xishuangbanna, Southwest China - Xuyan Liu; Siwen Wang; Qianqian Zhang; Chunlai Jiang; Linlin Liang; Shihao Tang; Xingying Zhang; Xiuzhen Han; Lin Zhu (Journal of Environmental Sciences, 2023)

Engelheptanoxides behave as liver X receptor α agonists - Yu-Hsuan Liang; Yu-Han Luo; Ih-Sheng Chen; Hsiang-Ru Lin (Medicinal Chemistry Research, 2023)

A label-free PEC aptasensor platform based on g-C3N4/BiVO4 heterojunction for tetracycline detection in food analysis - Zhengzheng Zhao; Zhifang Wu; Xueling Lin; Fangjie Han; Zhishan Liang; Likun Huang; Mengjiao Dai; Dongxue Han; Lipeng Han; Li Niu (Food Chemistry, 2023)

The impacts of urban anthropogenic heat and surface albedo change on boundary layer meteorology and air pollutants in the Beijing-Tianjin-Hebei region - Ruiting Liu; Zhiwei Han; Jiawei Li; Jie Li; Lin Liang; Yunfei Wu (Urban Climate, 2023)

Higher blood selenium level is associated with lower risk of hyperhomocysteinemia in the elderly - Ting Wang; Liqin Su; Xi Chen; Sisi Wang; Xu Han; Yibin Cheng; Shaobin Lin; Liang Ding; Jingyi Liu; Chen Chen; Frederick W. Unverzagt; Ann M. Hake; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Residue behaviors, processing factors and transfer rates of pesticides and metabolites in rose from cultivation to consumption - Yanli Bian; Yizhi Feng; Aijuan Zhang; Xiaoxue Qi; Xingang Ma; Jinju Pan; Jifeng Han; Lin Liang (Journal of Hazardous Materials, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Chromosomal mapping of a locus associated with adult-stage resistance to powdery mildew from Agropyron cristatum chromosome 6PL in wheat - Yida Lin; Shenghui Zhou; Xuezhong Liang; Baojin Guo; Bing Han; Haiming Han; Jingpeng Zhang; Yuqing Lu; Zhi Zhang; Xinming Yang; Xiuquan Li; Weihua Liu; et al. (Theoretical and Applied Genetics, 2022)

A short review of probabilistic slope stability analysis considering spatial variability of geomaterial parameters - Wengang Zhang; Xin Gu; Liang Han; Jiahao Wu; Zhiwei Xiao; Maoyi Liu; Lin Wang (Innovative Infrastructure Solutions, 2022)

Probabilistic stability analysis of embankment slopes considering the spatial variability of soil properties and seismic randomness - Wen-gang Zhang; Jia-hao Wu; Xin Gu; Liang Han; Lin Wang (Journal of Mountain Science, 2022)

The lining responses for shallow mountain tunnels subjected to frost heaving - Xian-zhang Ling; Yuan Yu; Liang Tang; Lin Geng; Xiao Han (Journal of Mountain Science, 2022)

The brown root rot fungus Phellinus noxius affects microbial communities in different root‐associated niches of Ficus trees - Tse‐Yen Liu; Chao‐Han Chen; Yu‐Liang Yang; Isheng J. Tsai; Ying‐Ning Ho; Chia‐Lin Chung (Environmental Microbiology, 2022)
Summary Brown root rot (BRR) caused by Phellinus noxius is a destructive tree disease in tropical and subtropical areas. To understand how BRR affects the composition of the plant rhizoplane‐enriched microbiota, the microbiomes within five root‐associated compartments (i.e., bulk soil, old/young root rhizosphere soil, old/young root tissue) of Ficus trees naturally infected by P. noxius were investigated. The level of P. noxius infection was determined by quantitative PCR. Illumina sequencing of the internal transcribed spacer and 16S rRNA revealed that P. noxius infection caused a significant reduction in fungal diversity in the bulk soil, the old root rhizosphere soil, and the old root tissue. Interestingly, Cosmospora was the only fungal genus positively correlated with P. noxius . The abundance and composition of dominant bacterial taxa such as Actinomadura , Bacillus , Rhodoplanes , and Streptomyces differed between BRR‐diseased and healthy samples. Furthermore, 838 isolates belonging to 26 fungal and 35 bacterial genera were isolated and tested for interactions with P. noxius . Antagonistic activities were observed for isolates of Bacillus , Pseudomonas , Aspergillus , Penicillium , and Trichoderma . Cellophane overlay and cellulose/lignin utilization assays suggested that Cosmospora could tolerate the secretions of P. noxius and that the degradation of lignin by P. noxius may create suitable conditions for Cosmorpora growth.

Interaction between the cell walls of microalgal host and fungal carbohydrate‐activate enzymes is essential for the pathogenic parasitism process - Juan Lin; Hailong Yan; Liang Zhao; Yanhua Li; Bahareh Nahidian; Mianmian Zhu; Qiang Hu; Danxiang Han (Environmental Microbiology, 2021)
Summary Fungi can parasitize microalgae, exerting profound impacts on both the aquatic ecosystems and microalgal mass cultures. In this study, the unicellular green alga Haematococcus pluvialis and the blastocladialean fungus Paraphysoderma sedebokerense were used as a model system to address the mechanisms underlying the fungal parasitism on the algal host. High‐throughput metabolic assay indicated that P . sedebokerense can utilize several carbon sources with a preference for mannose, glucose and their oligosaccharides, which was compatible with the profile of the host algal cell walls enriched with glucan and mannan. The results of dual transcriptomics analysis suggested that P . sedebokerense can upregulate a large number of putative carbohydrate‐activate enzymes (CAZymes) encoding genes, including those coding for the endo‐1,4‐β‐glucanase and endo‐1,4‐β‐mannanase during the infection process. The cell walls of H . pluvialis can be decomposed by both P . sedebokerense and commercial CAZymes (e.g. cellulase and endo‐1,4‐β‐mannanase) to produce mannooligomers, while several putative parasitism‐related genes of P . sedebokerense can be in turn upregulated by mannooligomers. In addition, the parasitism can be blocked by interfering the selected CAZymes including glucanase, mannanase and lysozyme with the specific inhibitors, which provided a framework for screening suitable compounds for pathogen mitigation in algal mass culture.

Development of a TaqMan loop-mediated isothermal amplification assay for the rapid detection of pigeon paramyxovirus type 1 - Ruiying Liang; Lin Liang; Xiaoxia Ren; Yaxiong Jia; Kun Han; Jingjie Zhao; Cuiping Song; Shangjin Cui (Archives of Virology, 2021)

At3g53630 encodes a GUN1-interacting protein under norflurazon treatment - Xing-Qi Huang; Lin-Juan Wang; Meng-Juan Kong; Na Huang; Xin-Ya Liu; Han-Yu Liang; Jia-Xin Zhang; Shan Lu (Protoplasma, 2021)

Photosensitive hydrogels: from structure, mechanisms, design to bioapplications - Wenhui Ji; Qiong Wu; Xisi Han; Wei Zhang; Wei Wei; Liang Chen; Lin Li; Wei Huang (Science China Life Sciences, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

Neo-debromoaplysiatoxin C, with new structural rearrangement, derived from debromoaplysiatoxin - Yang-Hua Tang; Ting-Ting Liang; Ting-Ting Fan; Lawrence Jordan Keen; Xiao-Dan Zhang; Lin Xu; Qi Zhao; Rong Zeng; Bing-Nan Han (Natural Product Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Endothelial Notch activation promotes neutrophil transmigration via downregulating endomucin to aggravate hepatic ischemia/reperfusion injury - Peiran Zhang; Kangyi Yue; Xinli Liu; Xianchun Yan; Ziyan Yang; Juanli Duan; Congcong Xia; Xinyuan Xu; Mei Zhang; Liang Liang; Lin Wang; Hua Han (Science China Life Sciences, 2020)

Effects of Temperature on Bacterial Biodiversity and Qualities of Fermented Yucha Products - Shuai Wang; Jing Han; Jingbo Zhang; Xinping Lin; Huipeng Liang; Shengjie Li; Xiuping Dong; Chaofan Ji (Journal of Aquatic Food Product Technology, 2020)

Bin-based genome-wide association analyses improve power and resolution in QTL mapping and identify favorable alleles from multiple parents in a four-way MAGIC rice population - Zhongmin Han; Gang Hu; Hua Liu; Famao Liang; Lin Yang; Hu Zhao; Qinghua Zhang; Zhixin Li; Qifa Zhang; Yongzhong Xing (Theoretical and Applied Genetics, 2020)

Circ_ANKIB1 stabilizes the regulation of miR-19b on SOCS3/STAT3 pathway to promote osteosarcoma cell growth and invasion - Yi-xin Du; Lin-xin Guo; Han-song Pan; Yi-min Liang; Xiang Li (Human Cell, 2020)

Marine 3D seismic volumes from 2D seismic survey with large streamer feathering - Liang-Fu Lin; Ho-Han Hsu; Char-Shine Liu; Kuo-Han Chao; Chia-Chun Ko; Shye-Dong Chiu; Hsin-Sung Hsieh; Yu-Fang Ma; Song-Chuen Chen (Marine Geophysical Research, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Characterization of some selected mud volcanoes of southern Taiwan - Arvind Kumar; Tsung-Han Yang; Vivek Walia; Yi-Chun Sung; Hasio-Fen Lee; Shih-Jung Lin; Kuo-Liang Wen (Acta Geophysica, 2018)

Phenolic acid production is more effectively enhanced than tanshinone production by methyl jasmonate in Salvia miltiorrhiza hairy roots - Bingcong Xing; Dongfeng Yang; Lin Liu; Ruilian Han; Yanfang Sun; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

Sonic Hedgehog Regulation of the Neural Precursor Cell Fate During Chicken Optic Tectum Development - Ciqing Yang; Xiaoying Li; Qiuling Li; Han Li; Liang Qiao; Zhikun Guo; Juntang Lin (Journal of Molecular Neuroscience, 2018)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Mechanistic and therapeutic perspectives for cardiac arrhythmias: beyond ion channels - Yufei Wu; Jun Li; Liang Xu; Li Lin; Yi-Han Chen (Science China Life Sciences, 2017)

Retraction Note to: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Relation of Transcriptional Factors to the Expression and Activity of Cytochrome P450 and UDP-Glucuronosyltransferases 1A in Human Liver: Co-Expression Network Analysis - Shilong Zhong; Weichao Han; Chuqi Hou; Junjin Liu; Lili Wu; Menghua Liu; Zhi Liang; Haoming Lin; Lili Zhou; Shuwen Liu; Lan Tang (The AAPS Journal, 2017)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Allergy symptoms, serum total immunoglobulin E, and risk of head and neck cancer - Hsiao-Chen Liao; Shang-Yin Wu; Chun-Yen Ou; Jenn-Ren Hsiao; Jehn-Shyun Huang; Sen-Tien Tsai; Cheng-Chih Huang; Tung-Yiu Wong; Wei-Ting Lee; Ken-Chung Chen; Sheen-Yie Fang; Jiunn-Liang Wu; et al. (Cancer Causes & Control, 2016)

RETRACTED ARTICLE: Effect of Anti-Sticking Nanostructured Surface Coating on Minimally Invasive Electrosurgical Device in Brain - Han-Yi Cheng; Keng-Liang Ou; Hsi-Jen Chiang; Li-Hsiang Lin (Annals of Biomedical Engineering, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

Microstructural and mineral analysis on the fault gouge in the coseismic shear zone of the 2008 M w 7.9 Wenchuan earthquake - Ren-mao Yuan; Bing-liang Zhang; Xi-wei Xu; Chuan-yong Lin; Zhu-jun Han (International Journal of Earth Sciences, 2015)

A Simple and Efficient Method for Breast Cancer Diagnosis Based on Infrared Thermal Imaging - Fei Han; Guilian Shi; Chengwen Liang; Lin Wang; Kaiyang Li (Cell Biochemistry and Biophysics, 2015)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

The fusion protein Penhrp containing Penaeidin-2 and HarpinZ induced a stronger hypersensitive response and systemic acquired resistance in tobacco comparing to the original HarpinZ - Han Xia; Jin-Ping Xu; Xiao-Lin Meng; Zhuo Liang; Jian Wang (Australasian Plant Pathology, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Cloning and characterization of a wheat β-1,3-glucanase gene induced by the stripe rust pathogen Puccinia striiformis f. sp. tritici - Bo Liu; Xiaodan Xue; Suping Cui; Xiaoyu Zhang; Qingmei Han; Lin Zhu; Xiaofei Liang; Xiaojie Wang; Lili Huang; Xianming Chen; Zhensheng Kang (Molecular Biology Reports, 2010)

Increasing trend of the incidence of esophageal squamous cell carcinoma, but not adenocarcinoma, in Taiwan - Ching-Liang Lu; Hui-Chu Lang; Jiing-Chyuan Luo; Chun-Chu Liu; Han-Chieh Lin; Full-Young Chang; Shou-Dong Lee (Cancer Causes & Control, 2010)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Specific Phage-Displayed Peptides Binding to Tumor Vasculature - Yu Han; Liu Hong; Kaichun Wu; Shuhui Liang; Lin Xia; Shanshan Cao; Huihong Zhai; Jun Wang; Lijie He; Feihu Bai; Zhen Chen; Taidong Qiao; et al. (International Journal of Peptide Research and Therapeutics, 2006)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)